Sovereign Credit Risk Interdependencies and Shock Transmission Across Countries and Maturities in BRICS - Suissi, Nada; Abid, Amira (Journal of Ecohumanism, 2025)
This study examines the interconnectedness of sovereign credit risk across BRICS countries and different maturities, focusing on the transmission of shocks within the Credit Default Swap (CDS) market. Using the Time-Varying Parameter Vector Autoregression (TVP-VAR) methodology, we analyze daily sovereign CDS spreads for maturities of 6 months, 5 years, and 10 years from June 2018 to April 2022. The results reveal significant co-movements among BRICS CDS spreads, with distinct patterns across countries and maturities. Brazil and China emerge as key transmitters of shocks over medium and long terms, while South Africa shows rapid responses to short-term changes. Conversely, India and China act as net receivers of shocks, highlighting varying sensitivities across time horizons. This research provides fresh insights into the dynamic interplay of sovereign credit risk within BRICS, emphasizing both country-specific and maturity-related dimensions. The findings have practical implications for investors and policymakers, suggesting the need for enhanced economic policy coordination, including central bank collaboration and the creation of monitoring and research mechanisms to bolster economic resilience and mitigate systemic risks.